Uji Toleransi Bayam Merah Terhadap Cekaman Salinitas - Halim, Bruari (Jurnal Sains Pertanian Equator, 2020)
This research aimed to know level of tolerance red spinach to salinity stress. This research was conducted in Pontianak from July 9th to August 2nd 2019. The method used was the completely randomized design (CRD). Comprised of 6 concentration level. Concentration level was the: 0, 2.000, 4.000, 6.000, 8.000 and 10.000 ppm. The variables observed in this research were fresh weight, root volume, leaf area, root dry weight and shoot dry weight. The results showed that the red spinach was tolerance the salinity stress of 8.000 ppm NaCl but the more salt accumulation increased the stunted growth.Keywords : Tolerance Test, Red Spinach, Salinity Stress